2018
DOI: 10.1007/s12029-018-0062-y
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Impact of PI3K/BRAF Mutations in RAS Wild Metastatic Colorectal Cancer: Meta-analysis Results

Abstract: This analysis suggests that patients with mCRC and either PI3K or BRAF mutation may have a lower response and worse outcome when treated with anti-EGFR in the first line. Given their worse outcome, routine testing for BRAF and PI3K mutational status should be considered. Novel therapeutic approaches are needed for patients with mutations in BRAF or PI3K.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…In the present study, our results suggested that BRAF mutation was associated with shorter OS in both MSS CRC patients and MSI CRC patients overall and in all subgroups stratified by cancer type, tumor stage, and treatment, which were similar with the prognostic value of BRAF mutation in entire CRC and mCRC. 79 84 Similar to the previous results, we also found the poor prognostic effects of BRAF mutation in both MSS and MSI CRC treated with surgery and adjuvant therapy, and MSI did not change the poor effect of BRAF mutation. 85 Our results also revealed that MSI was not associated with OS in BRAF wt patents with CRC overall or in stage I–III CRC, similar to the study by Gkekas et al 78 performed in stage II CC regardless of BRAF mutation.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In the present study, our results suggested that BRAF mutation was associated with shorter OS in both MSS CRC patients and MSI CRC patients overall and in all subgroups stratified by cancer type, tumor stage, and treatment, which were similar with the prognostic value of BRAF mutation in entire CRC and mCRC. 79 84 Similar to the previous results, we also found the poor prognostic effects of BRAF mutation in both MSS and MSI CRC treated with surgery and adjuvant therapy, and MSI did not change the poor effect of BRAF mutation. 85 Our results also revealed that MSI was not associated with OS in BRAF wt patents with CRC overall or in stage I–III CRC, similar to the study by Gkekas et al 78 performed in stage II CC regardless of BRAF mutation.…”
Section: Discussionsupporting
confidence: 89%
“…Multiple meta-analyses were performed in mCRC to explore the associations of BRAF mutation with prognosis and achieved consistent results that BRAF mutation was significantly associated with shorter PFS and OS. 80 84 In stage II–III CRC treated with surgery and adjuvant therapy, BRAF mutation was also found to be associated with shorter OS and DFS. 85 However, there was no meta-analysis study summarizing the prognosis of the CRC patients with different subtypes defined by MSI and BRAF mutation, ie, MSS/ BRAF wt, MSS/ BRAF mut, MSI/ BRAF wt, and MSI/ BRAF mut.…”
Section: Discussionmentioning
confidence: 99%
“…Smeby et al concluded that the role of genetic alterations may depend on molecular backgrounds; it may therefore be concluded that the association of PIK3CA mutations with clinicopathologic characteristics depends on distinct molecular contexts [62]. Since numerous studies have demonstrated the prognostic and predictive value of PIK3CA mutations in KRAS-wild CRC, the association between PIK3CA mutations and clinicopathologic features in wild-type KRAS may differ from unselected patients [6,59,63].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of PTEN loss and mutation was 19%-58% and 7%-9%, respectively, in patients with wildtype KRAS mCRC [19,[24][25][26][27] . For those patients with wild-type KRAS exon 2 mCRC, PIK3CA mutation and PTEN alterations were associated with poorer objective response rate and OS for anti-EGFR therapy in two metanalyses [28,29] . However, there might be different predictive effects between different PIK3CA mutations and different techniques detecting PTEN alterations.…”
Section: Other Biomarkersmentioning
confidence: 95%